Yawning Heights by A. A. Zinoviev as a Model of Philosophical Dystopia - Elena Gennadievna Serebryakova (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2024)
This article analyses A. A. Zinoviev’s dystopia Yawning Heights. The author substantiates the thesis about the fundamental difference between philosophical and artistic dystopias. In the author’s opinion, the fundamental difference is rooted in the scientific and artistic methods of cognition of the world, specific ways of creating philosophical and artistic pictures of the world, and types of narrative. The author of a literary text moves towards a model of the world from an artistic image. The philosophical picture of the world presupposes a conceptual vision of the world and evidence-based argumentation of this concept. This methodological difference entails unique author’s strategies that determine the poetics and style of philosophical and literary texts. The emotional-sensual perception of the world by the author of a literary text determines the type of narrative in which the logical-analytical approach to reality is secondary in comparison with the figurative one. For scientific thinking, the analyticity and infallibility of conclusions are primary. The philosophical approach presupposes integrity, and in a certain sense completeness. The artistic picture of the world is focused on a dialogue with the reader, and therefore on the additional construction of the semantics of the text through the reader’s experience. The dystopia Yawning Heights is evaluated by the author of the article as a scientific but not a literary text. Observation, analysis, hypothesis, and assumption are a tool for analysing social reality, in which, according to Zinoviev, there are universal laws that are common to any human community and social system. The philosopher transfers the scientific method into the novel, moves in the comprehension of social laws from the abstract to the particular, i.e., from society to the individual. Zinoviev uses mask characters to evaluate the laws of sociality that depersonalise a person. The method, which is also typical of a literary text, receives a special interpretation from the philosopher. The schematic character of images reflects a law common to all social individuals, in which the particular is subordinate to the general, and psychological and personal differences are leveled. Zinoviev created a special genre — a philosophical dystopia, which is guided not by artistic, but by scientific logic.